2022
DOI: 10.3343/alm.2022.42.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific U-Shaped Relationships Between High-Density Lipoprotein Cholesterol Levels and 10-year Major Adverse Cardiovascular Events: A Nationwide Cohort Study of 5.7 Million South Koreans

Abstract: Background: High-density lipoprotein cholesterol (HDL-C) is a well-known predictor of atherosclerotic cardiovascular diseases (ASCVD). We explored the relationships between HDL-C levels and 10-year major adverse cardiovascular events (MACE) and provided sexspecific upper reference limits for HDL-C levels. Methods: Based on the Korean National Health Insurance Sharing Service, we identified 5,703,897 subjects (women, 48%) with age ≥ 40 years, eligible HDL-C results, and no prior ASCVD in 2009. We investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…These values, however, do not adequately account for the role gender and race play in the development of CVD when HDL-C is extremely elevated. A retrospective study showed that HDL-C>90 mg/dL among males had an increased 10 year associated risk of major adverse cardiac events, whereas women had a similar risk at HDL-C >130 mg/dL [21] . Variability in HDL-C amongst race and ethnic groups have been identified, but their implications are unknown.…”
Section: Elevated High Density Lipoprotein-cmentioning
confidence: 99%
“…These values, however, do not adequately account for the role gender and race play in the development of CVD when HDL-C is extremely elevated. A retrospective study showed that HDL-C>90 mg/dL among males had an increased 10 year associated risk of major adverse cardiac events, whereas women had a similar risk at HDL-C >130 mg/dL [21] . Variability in HDL-C amongst race and ethnic groups have been identified, but their implications are unknown.…”
Section: Elevated High Density Lipoprotein-cmentioning
confidence: 99%
“…The Apo B level can be conveniently measured at low cost in routine clinical laboratories and the measurements are more accurate than those of LDL-C or non-HDL-C [6]. Further in-depth study and evaluation are required to validate the recently proposed candidate primary markers for accurate ASCVD risk assessment [12,13]. Continuous efforts to determine the best way for ASCVD risk assessment and treatment target are required.…”
Section: Editorialmentioning
confidence: 99%
“…One of the problems with HDL particle analysis for diagnostic purposes has been the extreme complexity of these particles and the lack of resolution of older measurement tools. For example, although high HDL-cholesterol (HDL-C) concentrations have been found to be protective against CVD, several large recent studies demonstrated that the relationship between HDL-C concentration and adverse health outcomes tends to follow a U-shaped curve, with both low HDL-C and very high HDL-C being associated with increased cardiovascular (CV) events (21)(22)(23). Clearly, it is not simply the measurement of the total amount of cholesterol carried within HDL that is diagnostic, but rather some other aspect of HDL that is critical, whether it be compositional, structural, or functional.…”
Section: Hdl Glycosylation Profiling For Diagnostic Purposesmentioning
confidence: 99%